Concise Review: Skeletal Muscle as a Delivery Route for Mesenchymal Stromal Cells - Hamidian Jahromi, Shiva (Stem Cells Transl Med, 2019)
Mesenchymal stromal cells (MSCs) have demonstrated extensive capacity to modulate a catabolic microenvironment toward tissue repair. The fate, biodistribution, and dwell time of the in vivo delivered MSCs largely depend on the choice of the cell delivery route. Intramuscular (IM) delivery of MSCs is clinically safe and has been used for the effective treatment of local pathologies. Recent findings have shown that the secretome of the IM‐delivered MSCs enters the circulation and provides systemic effects on distant organs. In addition, muscle tissue provides a safe residence for the delivered MSCs and an extended secretorily active dwell time compared with other delivery routes. There are, however, controversies concerning the fate of MSCs post IM‐delivery and, specifically, into an injured site with proinflammatory cues. This review seeks to provide a brief overview of the fate and efficacy of IM‐delivered MSCs and to identify the gaps that require further assessment for adoption of this promising route in the treatment of systemic disease. stem cells translational medicine 2019;8:456–465